Cesar Moro and an identity in conflict. Symbolism, psychoanalysis, surrealism and abstraction of the Peruvian art - Villegas, Fernando (2017)
This paper aims to study the artistic references of Cesar Moro and the importance of his work in the development of Peruvian art. We know that Moro met the Symbolism proposal bequeathed by Jose Maria Eguren, in addition to be familiarized with the psychoanalysis in Lima before his trip to Paris, where he would meet the surrealist group. It would be in the twenties when he displayed a proposal linked to the abstraction and Cubist geometry. Another important point of this article is to explore the identity of Moro through his art and his own representation: portraits and photographs. In both, there is a connection of how he assumes to be represented as in how he performed his works. He was born with the name of Alfredo Quispez Asin and he changed to Cesar Moro. The adoption of a new name implies the option to recognize himself as an artist forging a new identity whose creative vision is multiple. We will focus on how he wanted to be represented through portraits and photography. In this way, it is attempted to understand how he manifested an indisputable unit both in the creative process of the artist and in a written text and image.